Pelatihan Pembuatan Aplikasi E-raport dengan Menggunakan Microsoft Office Excel Bagi Guru-guru SD di Wilayah Insana Fafinesu - Grandianus Seda Mada; Faustianus Luan; Oktovianus R. Sikas; Nugraha K. F. Dethan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The activity of filling in school data, student data, and student final grades in report card at elementary schools in the Insana Fafinesu District, Timor Tengah Utara Regency has been carried out in handwriting (conventional), which have some constraints such as taking a long time to processing grades, has a tendency to miscalculation if the student report card is lost or damaged, it does not have documentation/ back-up documents. For teachers who have sloppy handwriting, it will be difficult for a parent to read. One software that can be used in making student report cards is Microsoft Office Excel. This software is easy to understand and can overcome problems in making student report cards such as the length of time for processing grades, the tendency of grade processing error, difficulties in reading teacher writing by parents, and overcoming problems with documentation/backup documents. This service activity aims to provide training in making e-report card applications using Microsoft Excel for elementary school teachers in the Insana Fafinesu area, Timor Tengah Utara Regency. The methods used in this activity are workshops and ongoing mentoring. As a result, teachers better understand the functions in Microsoft Excel that are useful in the process of filling out student report cards, each teacher succeeds in making their own e-reports, and they agree that e-reports with Microsoft Excel are more efficient and effective than filling out report cards manually (conventional) and will use e-reports in their respective schools. The next plan for this service activity will be an application for Teacher Performance Assessment (TPA) and Employee Work Targets (EWT).